Protective Effects of Carnosol on Renal Interstitial Fibrosis in a Murine Model of Unilateral Ureteral Obstruction - Jae-Hyung Park; Jaechan Leem; Sun-Jae Lee (MDPI AG, 2022)
Renal fibrosis is a common feature of chronic kidney disease and is a promising therapeutic target. However, there is still limited treatment for renal fibrosis, so the development of new anti-fibrotic agents is urgently needed. Accumulating evidence suggest that oxidative stress and endoplasmic reticulum (ER) stress play a critical role in renal fibrosis. Carnosol (CS) is a bioactive diterpene compound present in rosemary plants and has potent antioxidant and anti-inflammatory properties. In this study, we investigated the potential effects of CS on renal injury and fibrosis in a murine model of unilateral ureteral obstruction (UUO). Male C57BL/6J mice underwent sham or UUO surgery and received intraperitoneal injections of CS (50 mg/kg) daily for 8 consecutive days. CS improved renal function and ameliorated renal tubular injury and interstitial fibrosis in UUO mice. It suppressed oxidative injury by inhibiting pro-oxidant enzymes and activating antioxidant enzymes. Activation of ER stress was also attenuated by CS. In addition, CS inhibited apoptotic and necroptotic cell death in kidneys of UUO mice. Furthermore, cytokine production and immune cell infiltration were alleviated by CS. Taken together, these findings indicate that CS can attenuate renal injury and fibrosis in the UUO model.